Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.immuni.2011.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Smad-Independent T Helper 17 Cell Induction by Transforming-Growth Factor-β Is Mediated by Suppression of Eomesodermin

Abstract: Transforming growth factor-β (TGF-β) has been shown to be required for Th17 cell differentiation via Smad-independent mechanisms. The molecular mechanism underlying this pathway remains to be clarified, however. We searched for genes regulated by TGF-β through the Smad-independent pathway by using Smad2 and Smad3 double-deficient T cells and identified the transcription factor Eomesodermin (Eomes), whose expression was suppressed by TGF-β via the c-Jun N-terminal kinase (JNK)-c-Jun signaling pathway. Inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
104
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 66 publications
12
104
0
Order By: Relevance
“…Accordingly, we did not observe Eomes expression in IL-17-producing cells in vivo. The described Eomes-mediated Th17 repression was not complete, suggesting perhaps that there may be other pathways of Rorc and Il17 induction that are not inhibited by Eomes (26). In agreement with a minor role of Eomes for the inhibition of Th17 responses, we did not observe a significant increase in the frequency or total numbers of CD4 + Th17 cells in Eomes-KO mice either during the inflammatory response in colitis or during aging.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Accordingly, we did not observe Eomes expression in IL-17-producing cells in vivo. The described Eomes-mediated Th17 repression was not complete, suggesting perhaps that there may be other pathways of Rorc and Il17 induction that are not inhibited by Eomes (26). In agreement with a minor role of Eomes for the inhibition of Th17 responses, we did not observe a significant increase in the frequency or total numbers of CD4 + Th17 cells in Eomes-KO mice either during the inflammatory response in colitis or during aging.…”
Section: Discussionsupporting
confidence: 75%
“…Previous reports indicate that Eomes RNA and protein are induced upon activation in vitro (8,26). Indeed, after 3 d of in vitro stimulation with anti-CD3 and IL-2, we found that a substantial fraction of cultured CD4 + CD45RB high T cells expressed Eomes (Fig.…”
Section: Eomes + Cd4 + T Cells Accumulate With Agesupporting
confidence: 58%
See 3 more Smart Citations